A fungal endosymbiont affects host plant recruitment through seed- and litter-mediated mechanisms - Omacini, Marina (2009)
1.Many grass species are associated with maternally transmitted fungal endophytes. Increasing evidence shows that endophytes enhance host plant success under varied conditions, yet studies have rarely considered alternative mechanisms whereby these mutualistic symbionts may affect regeneration from seed. 2.We performed a microcosm experiment to evaluate whether infection with Neotyphodium occultans affects recruitment in the annual grass Lolium multiflorum either directly, by infecting the seeds, or indirectly, by altering the suitability of recruitment microsites through the litter shed by host plants. Endophyte effects on establishment were tested for different litter depths and watering regimes under natural herbivory by leaf-cutting ants. Seed infection increased seedling emergence through the litter as well as final recruitment, irrespective of microsite conditions. However, litter produced by infected plants delayed emergence and decreased density of both infected and non-infected grass populations. Individual plant biomass did not change with seed infection but was increased under deep litter from endophyte-infected plants. Although seed infection did not protect establishing plants from leaf-cutting ants, herbivory was reduced in the presence of deep litter shed by infected plants. We conclude that fungal endophytes may affect host plant recruitment across subsequent generations not only by infecting the seeds but also through the host's dead remains. While the former effect entailed an advantage to infected plants, litter-mediated effects did not discriminate by infection status, and generally promoted the establishment of fewer and larger plants. Thus hidden foliar symbionts may play an underappreciated role in maintaining host species dominance through the litter produced by prior patch occupants.